2016
DOI: 10.1103/physrevlett.116.087202
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Magnetothermopower in a Metallic Frustrated Antiferromagnet

Abstract: We report the temperature T and magnetic field H dependence of the thermopower S of an itinerant triangular antiferromagnet PdCrO 2 in high magnetic fields up to 32 T. In the paramagnetic phase, the zerofield thermopower is positive with a value typical of good metals with a high carrier density. In marked contrast to typical metals, however, S decreases rapidly with increasing magnetic field, approaching zero at the maximum field scale for T > 70 K. We argue here that this profound change in the thermoelectri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
(70 reference statements)
1
23
0
1
Order By: Relevance
“…[ 2,15–17 ] Moreover, as the isostructural compounds, PtCoO 2 has the lowest room temperature resistivity amongst the oxide system known, [ 1 ] and PdCrO 2 shows strong coupling between the antiferromagnetism and the conduction electrons. [ 18,19 ] Growing PtCoO 2 and PdCrO 2 thin films will expand the fundamental investigations and further potential applications of metallic delafossite oxides. In fact, thin films of PtCoO 2 and PdCrO 2 have been fabricated by rf‐sputtering about 40 years ago, [ 20 ] but the room temperature conductivity is around one order of magnitude inferior than recent reported single‐crystals.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,15–17 ] Moreover, as the isostructural compounds, PtCoO 2 has the lowest room temperature resistivity amongst the oxide system known, [ 1 ] and PdCrO 2 shows strong coupling between the antiferromagnetism and the conduction electrons. [ 18,19 ] Growing PtCoO 2 and PdCrO 2 thin films will expand the fundamental investigations and further potential applications of metallic delafossite oxides. In fact, thin films of PtCoO 2 and PdCrO 2 have been fabricated by rf‐sputtering about 40 years ago, [ 20 ] but the room temperature conductivity is around one order of magnitude inferior than recent reported single‐crystals.…”
Section: Introductionmentioning
confidence: 99%
“…1a, PdCrO 2 has a delafossite structure, consisting of stacked layers of highly conducting Pd layers sandwiched between planes of Mott-insulating CrO 2 (refs 7, 8). The Cr ions have a localized spin of 3/2 and are highly frustrated, forming a non-coplanar and non-collinear antiferromagnetic 120° helical structure at T N =37.5 K (refs 7, 9, 10, 11, 12). Quantum oscillation813 and angle-resolved photoemission studies14 have mapped out the Fermi surface (FS) of PdCrO 2 .…”
mentioning
confidence: 99%
“…A recent magnetothermopower study also revealed a strong interaction between the 4 d 9 electrons and the short-range spin correlations persisting well above T N (ref. 10). …”
mentioning
confidence: 99%
“…Older polycrystalline samples [25] may have been further from stoichiometry. There are also discrepancies between results on PdCrO 2 single crystals [58,61]. so far not been possible to measure the out-of-plane Seebeck coefficient, however the measured in-plane values are in good agreement with the calculations [50].…”
Section: Thermoelectricitymentioning
confidence: 68%
“…However, Ref. [61] reports a Seebeck coefficient with a rather different temperature dependence. It also shows a strong suppression under intense magnetic fields, which is not seen in the moderate applied fields used in Ref.…”
Section: Thermoelectricitymentioning
confidence: 99%